Online computer lab booking system / Rabiatul Adawiah Hasyim - Hasyim, Rabiatul Adawiah (2012)
Booking computer lab is still using manual system in SK Abu Bakar, Mentakab, Pahang. It involves several processes in which teachers have to register and book manually in the log book. Manual system is considered to be costly and time consuming as it requires a lot of documentation and large space of filing cabinets to store data. Online Computer Lab Booking System is developed in order to overcome the problems encountered within the manual system. The methodology used in the development of the system is System Development Life Cycle (SDLC). SDLC is the sequential phases or stages an information system (IS) follows throughout its useful life. The SDLC establishes a logical order or sequence in which the system development activities occur and indicates whether to proceed from one system development activity to the next through the phases of planning, analysis, design, implementation, and maintenance. The system is developed as a medium to help users efficiently reserve the computer lab. Apart from that, the system is developed to enhance the booking process through an online and users are allowed to access into the system anywhere at any time. For further study, the system can be applied to other schools around Pahang that have computer lab facilities.